The features of the organizational culture and its relationship to the organizational elements in the institution - Nassima BOUMAARAF (Social Sciences Journal, 1970)
We try through this article define the general features of organizational culture anddetermine its importance and identify its dimension and components and various forms. Wealso seek to clarify the relationship between organizational culture and other organizationalelements in the organization, and to clarify the nature of the reciprocal and complementaryrelationship between them